The somatotype and dermatoglyphic profiles of adult, junior and juvenile male Brazilian top-level volleyball players - Zary, J. C.; Reis, V. M.; Rouboa, A.; Silva, A. J.; Fernandes, P. R.; Filho, J. F. (Science & Sports, 2010)
The somatotype is believed to influence volleyball performance. Additionally, the impression of the digitals is also believed to assess the physical potential of athletes. The aim of the present study was to investigate the somatotype and dermatoglyphic profiles of players of three Brazilian national volleyball teams: adults, juvenile and infant-juvenile. Materials and methods A total of 38 male players included in the three national teams were observed. The subjects were submitted to an evaluation to identify the dermatoglyphic profile by means of fingerprints, following the protocol of Cummins and Midlo (1942). The digital impressions (DI) designs were used to determine the different patterns and the predominant types of digital form. The subjects were also submitted to an evaluation of the somatotype by the anthropometric method of Carter and Heath (1990).